KRITERIA NASABAH NON MUSLIM MENABUNG (PENGGALIAN DATA MENGGUNAKAN KLASIFIKASI ALGORITMA C4.5 _ STUDI KASUS DI PT. BANK BRI SYARIAH KANTOR CABANG MEDAN) - Nurbaiti Sirait (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2018)
Algorithm is a classification algorithm C4.5 decision tree data type (decision tree). C4.5 decision tree algorithm is built in three phases, namely the selection of attributes as root, create a branch for each value and divide the cases in the branch. These stages will be repeated for each branch until all cases the branches have the same class. Of the completion of the decision tree will produce some rule or knowledge of a case. In this thesis, the author classifies the criteria of non-Muslim customers save money in Islamic banks. The resulting rule greatly determined by the input variables in the set such as gender, age, religion, education level, employment and decision variables, namely customer saving and not saving. Application of C4.5 algorithm can determine the criteria that non-Muslim customers saving in PT. Bank BRI Syariah Kantor Cabang Medan